Private Payer's Status Improves Male Breast Cancer Survival. Issue 1 (28th October 2015) - Shi, Runhua; Taylor, Hannah; Liu, Lihong; Mills, Glenn; Burton, Gary
Abstract: Survival from male breast cancer is influenced by many factors. This study assessed payer's status effect on survival of male breast cancer patients. This study included 8, 828 male breast cancer patients diagnosed between 1998–2006 and followed to 2011 in the National Cancer Data Base. Cox regression was used to investigate the effect of payer's status and other factors on overall survival. Patients had 36.2%, 42.7%, 14.7%, and 6.5% of stage I to IV cancer, respectively. Payer status was private 47.7%, Medicare 42.6%, Medicaid 3.24%, unknown 3.59%, and uninsured 2.95%. Median overall survival (MOS) for all patients was 10.6 years. In multivariate analysis, Direct adjusted MOS was 12.46, 11.89, 9.99, 9.02, and 8.29 years for private, "unknown, " Medicare, uninsured, and Medicaid payer's status, respectively. Patients with private and "unknown" payer's status showed a significant difference in survival compared to uninsured patients, while Medicaid and Medicare patients did not. Age, race, stage, grade, income, comorbidity, distance travelled, and diagnosing/treating facility were also significant predictors of survival. Treatment delay and cancer program did not have a significant influence on survival.